2000
DOI: 10.1029/2000jb900015
|View full text |Cite
|
Sign up to set email alerts
|

How to relate body wave and surface wave anisotropy?

Abstract: Abstract. Seismic anisotropy is one of the most efficient geological and geodynamical tools for understanding the dynamics of the Earth. Upper mantle anisotropy is evident in seismic data sets for the last 30 years primarily from surface wave dispersion curves and body wave $K$ data. We demonstrate in this paper that surface wave and body wave derived anisotropy can be explained by the same anisotropic parameters (L• (7• (7•) in the simplest case of a horizontal fast sym-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
145
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(149 citation statements)
references
References 49 publications
(4 reference statements)
2
145
1
Order By: Relevance
“…We note, however, that there is a discrepancy in the shear wave splitting literature regarding the commutivity of the splitting operator in the low-frequency limit. Several theoretical studies have claimed that the splitting operators do not commute even at low frequency (e.g., Savage and Silver 1993;Wolfe and Silver 1998), while other workers have asserted that in the low-frequency limit the higher-order terms that lead to this noncommutivity can be discarded (Montagner et al 2000). Until this discrepancy is resolved, results based on the assumption of commutivity should be treated with some caution.…”
Section: Integration With Other Seismological Constraintsmentioning
confidence: 91%
See 2 more Smart Citations
“…We note, however, that there is a discrepancy in the shear wave splitting literature regarding the commutivity of the splitting operator in the low-frequency limit. Several theoretical studies have claimed that the splitting operators do not commute even at low frequency (e.g., Savage and Silver 1993;Wolfe and Silver 1998), while other workers have asserted that in the low-frequency limit the higher-order terms that lead to this noncommutivity can be discarded (Montagner et al 2000). Until this discrepancy is resolved, results based on the assumption of commutivity should be treated with some caution.…”
Section: Integration With Other Seismological Constraintsmentioning
confidence: 91%
“…There has been some theoretical progress on how to relate shear wave splitting to P wave traveltime residuals (e.g., Plomerová et al 1996;Schulte-Pelkum and Blackman 2003) and to surface wave observations (e.g. Montagner et al 2000). Extreme care must be taken, however, to properly account for the effect of vertically varying anisotropy and in particular for the fact that the shear wave splitting operator is non-commutative (Silver and Savage 1994;Wolfe and Silver 1998); some schemes for predicting shear wave splitting in common use may fail for vertically varying anisotropy.…”
Section: Integration With Other Seismological Constraintsmentioning
confidence: 99%
See 1 more Smart Citation
“…6b), and the SKS predictions themselves (Supplementary Fig. 6c) rely on a theory 30 that does not properly handle inclined symmetry axes and is only effective for rather long period waves.…”
Section: Resolution Issues and Model Testsmentioning
confidence: 99%
“…Therefore, results of crustal azimuthal anisotropy from receiver function analysis may still have some uncertainties due to the use of different methods and data selection criteria. Montagner et al (2000) derives formulas to compute the shear wave splitting time and fast axes from depthdependent G c,s and L, which provides a direct link between shear wave splitting measurements and shear wavespeed azimuthal anisotropy from surface wave data. For instance, Yao et al (2010) computed the contribution of shear wave splitting from crustal azimuthal anisotropy obtained from surface wave data and found that the thick crust in SE Tibet may contribute almost 1 s splitting time, which is close to b Depth-dependent shear wavespeed azimuthal anisotropy obtain from the NA: the black line for the magnitude of azimuthal anisotropy (K SV ) and the red bars for the direction of fast axes (U F ) in each layer (vertical for a N-S direction and horizontal for a E-W direction).…”
Section: Discussionmentioning
confidence: 99%